Teacher's Strategy in Developing Religious and Moral Values for Early Childhood in the Play Group of Al Mardhiyyah Samarinda - Ardiana, Reni (Educationist: Journal of Educational and Cultural Studies, 2023)
The formulation of the problem in this study is how to apply teacher strategies in developing religious and moral values in early childhood? And the purpose of this study is to describe the teacher's strategy in developing religious and moral abilities in early childhood. Data collection was carried out using several research techniques, the type of research used was qualitative research, the methods used to collect data were observation methods, interview methods, and documentation. the research subject was the Al Mardhiyyah Samarinda KB teacher. The research was conducted at KB Al Mardhiyyah Samarinda with the focus of the research being on teacher strategies in developing religious and moral abilities in early childhood at KB Al Mardhiyyah Samarinda. The results of the research from the teacher's strategy at KB Al Mardhiyyah Samarinda, namely that children are able to pray before and after carrying out activities properly and correctly, children are able to share with friends or others, children are able to say the word help well, from the results of the study it can be concluded that: teacher's strategy In developing the religious and moral abilities of children at KB Al Mardiyyah Samarinda, the implementation of activities to develop religious and moral values in early childhood can be carried out by means of routine activities or habituation, spontaneous or strengthening activities, and activities with examples or examples.